1986
DOI: 10.1177/019262338601400112
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Renal Disease in Dogs

Abstract: Renal disease is common in dogs. The incidence of significant renal disease increases with age. Many disease processes are subtle and subacute, and so many are not detected until they result in chronic renal failure. The causes of many renal diseases are not known but one must suspect immune-mediated damage in some.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Lymphohistiocytic infiltration, interstitial fibrosis, and swelling of glomeruli were related to the animal's age. This result supports previous studies that identified these changes as typical signs of aging in kidneys of rats and dogs [31–33].…”
Section: Discussionsupporting
confidence: 93%
“…Lymphohistiocytic infiltration, interstitial fibrosis, and swelling of glomeruli were related to the animal's age. This result supports previous studies that identified these changes as typical signs of aging in kidneys of rats and dogs [31–33].…”
Section: Discussionsupporting
confidence: 93%
“…The rapidity of calculi development has been shown in a rat model of urolithiasis in which calculi of heterogeneous composition were induced in Fischer 344 rats in less than two weeks by exposure to terephthalic acid or dimethyl terephthalate, both of which are associated with aciduria and hypercalciuria. 100 Beagles appear less predisposed to develop bladder calculi than a number of other breeds. 468,470 Bladder calculi are occasionally reported in laboratory cynomolgus monkeys.…”
Section: Inflammation Cystitismentioning
confidence: 89%
“…100,101 A membranous form of glomerulonephritis is described where there is little or no proliferation of the mesangium but the glomerular basement membrane is thickened and may show subepithelial spikes and focal or granular immunostaining for IgG and complement C3. 100,101 A membranous form of glomerulonephritis is described where there is little or no proliferation of the mesangium but the glomerular basement membrane is thickened and may show subepithelial spikes and focal or granular immunostaining for IgG and complement C3.…”
Section: Dogmentioning
confidence: 99%
“…C hronic kidney disease (CKD) is a major cause of morbidity and death in dogs and, given that it typically diagnosed relatively late in the course of the disease, dogs with advanced changes represent only a fraction of all dogs with CKD. 1,2 Human obesity is a risk factor for the development and progression of CKD, 3 and reducing body fat mass, either through dietary energy restriction or bariatric surgery, can reverse many of the associated clinical and nephropathologic manifestations. 4 Obesity is a common medical disorder in dogs, and can predispose to associated diseases such as osteoarthritis, respiratory disease, neoplasia, and insulin resistance.…”
mentioning
confidence: 99%